Integrasi Computational Thinking dalam Model EDP-STEM untuk Meningkatkan Kemampuan Berpikir Kritis Siswa SMP - Rahman, Abdul Aziz (Jurnal Didaktika Pendidikan Dasar, 2022)
This research is about the integration of Computational Thinking (CT) in the EDP STEM learning model using SimSketch modeling to improve students' critical thinking skills on the concept of the excretory system. SimSketch is a drawing and modeling tool. The research subjects were 8th graders. The research instruments were student worksheets and CT-integrated learning plans through SimSketch modeling, critical thinking skills tests, and questionnaires for students. This study found that the integration of CT with SimSketch modeling can be implemented in learning the concept of the excretory system. The findings of this study are that the integration of CT with SimSketch modeling can be implemented to increase motivation and demand for learning and students' critical thinking skills.